The orchid genomic toolkit - Gravendeel, Barbara (2018)
The application of genomic studies to orchids enables increasingly detailed discoveries of the evolution of both species and organs. We discuss different evolutionary questions that can be addressed using such approaches, and indicate optimal sequencing and data-handling solutions for each case. With this article we hope to promote the diversity of genomic research capitalizing the fascinating natural history of orchids that can now even be completed within the timeframe of a single PhD project.